ڕەخنەی مێژووخوازیی نوێ و گوتارە جیاوازەکانی چیرۆکی "لە خەوما"ی جەمیل سائیب - امین, د.باخان احمد حمە (Sulaimani Journal for Humanities, 2023)
This paper discusses a theory and new literary criticism for the analysis of literary and non-literary texts. in which It revisits some old historical issues that have been settled and it presents a new perspective for it. In the first part of this discussion, attention is paid to this type of criticism (the theoretical aspect of the discussion) and its aspects are discussed, In the other section, to better understand the criticism and practice it, we have quoted an old text which was written a century ago and that is the story of (in my dream) that was written by jamal saib. We have reinterpreted the different discourses of it according to this critique. The problems of this text and its theme have been discussed a lot before, but in this study, we have created new meanings and discourses. The aim of the research was to introduce the theory and the criticism through the analysis of the text, rather than the main purpose of the interpretation. Therefore, after evaluating the story, we have reached some new conclusions about the themes and discourses in the text, especially when we compared it to some contemporary historical evidence of the story. This was the opposite or addition to most other studies that were written on the subject. Hence, we have come to the importance and value of this criticism and necessity and activation in the field of research in literary and non-literary texts.
Keywords: criticism; new historicism; discourse; in my dream; theme